PENTINGNYA PERENCANAAN KEUANGAN PADA KELOMPOK USAHA MIKRO GUYUB RUKUN, PPA SHIKAR MALANG - Nony Kezia Marchyta; Widjojo Suprapto (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Financial planning is vital to the growth of micro-enterprises. The Guyub Rukun micro-enterprise group, owned by parents of children who are members of PPA Shikar in Malang, has encountered stagnation due to insufficient understanding of personal financial planning and entrepreneurial finance, which is harmful to business owners. Many micro-enterprise owners in the Guyub Rukun group merge their personal and business finances. Due to insufficient of mentors' managerial knowledge, these entrepreneurs need help managing their finances effectively. Therefore, community service activities by PPA Shikar Malang that highlight the significance of financial planning are crucial for the success of the Guyub Rukun micro-enterprise group. Training is provided in the form of personal and entrepreneurial financial planning. MSME entrepreneurs can immediately practice the knowledge by using the digital application for daily financial records and the MSME business financial records application on PlayStore. According to the questionnaires distributed to the participants, 92% expressed satisfaction, found the material easily understandable, and believed that community service activities benefited their micro-enterprises